Earth's evolving geodynamic regime recorded by titanium isotopes - Deng, Zhengbin; Schiller, Martin; Jackson, Matthew G.; Millet, Marc-Alban; Pan, Lu; Nikolajsen, Katrine; Saji, Nikitha S.; Huang, Dongyang; Bizzarro, Martin (Nature, 2023)
Earth's mantle has a two-layered structure, with the upper and lower mantle domains separated by a seismic discontinuity at about 660 km (refs. 1,2 ). The extent of mass transfer between these mantle domains throughout Earth's history is, however, poorly understood. Continental crust extraction results in Ti-stable isotopic fractionation, producing isotopically light melting residues 3–7 . Mantle recycling of these components can impart Ti isotope variability that is trackable in deep time. We report ultrahigh-precision 49 Ti/ 47 Ti ratios for chondrites, ancient terrestrial mantle-derived lavas ranging from 3.8 to 2.0 billion years ago (Ga) and modern ocean island basalts (OIBs). Our new Ti bulk silicate Earth (BSE) estimate based on chondrites is 0.052 ± 0.006‰ heavier than the modern upper mantle sampled by normal mid-ocean ridge basalts (N-MORBs). The 49 Ti/ 47 Ti ratio of Earth's upper mantle was chondritic before 3.5 Ga and evolved to a N-MORB-like composition between approximately 3.5 and 2.7 Ga, establishing that more continental crust was extracted during this epoch. The +0.052 ± 0.006‰ offset between BSE and N-MORBs requires that <30% of Earth's mantle equilibrated with recycled crustal material, implying limited mass exchange between the upper and lower mantle and, therefore, preservation of a primordial lower-mantle reservoir for most of Earth's geologic history. Modern OIBs record variable 49 Ti/ 47 Ti ratios ranging from chondritic to N-MORBs compositions, indicating continuing disruption of Earth's primordial mantle. Thus, modern-style plate tectonics with high mass transfer between the upper and lower mantle only represents a recent feature of Earth's history.